Abundance and temporal-spatial distribution of the rock shrimp Sicyonia dorsalis Kingsley, 1878 (Decapoda, Penaeoidea) from the northern coast of São Paulo state, Brazil. - Castilho, Antonio L.; Furlan, Michele; Costa, Rogério Caetano da [UNESP]; Fransozo, Vivian (My University, 2008)
Abundance and ecological distribution of the rock shrimp Sicyonia dorsalis from the northern coast of São Paulo State (Brazil) was investigated during a two-year period (July 2001 to June 2003). Monthly collections were conducted in the Ubatuba (UBA) and Caraguatatuba (CA) regions, using a commercial shrimp boat equipped with double-rig nets. In each region, seven depths were delimited (5 m to 35 m). A total of 1,752 and 1,894 shrimp were obtained at UBA and CA, respectively. The distribution of S. dorsalis differed among depths, years, and seasons. Highest abundance values were recorded in depths where silt and clay comprised more than 70% of the sediment. The majority (89%) of captured specimens were caught in the first year, in periods of lower mean temperature, mainly in the spring of 2001, when the intrusion of cold South Atlantic Central Waters (SACW) was more intense. In such period, the differences in the abundance of shrimps in each region (UBA = 1,118 and CA = 493) suggested that S. dorsalis migrated to the north (UBA), during the SACW intrusion. Thus, sediment type and water temperature are among the most important variables affecting the bathymetric distribution of S. dorsalis in these regions.